Identification and characterization of novel compound heterozygous variants in FSHR causing primary ovarian insufficiency with resistant ovary syndrome - Chen, Xiaopan; Chen, Linjie; Wang, Yang; Shu, Chongyi; Zhou, Yier; Wu, Ruifang; Jin, Bihui; Yang, Leixiang; Sun, Junhui; Qi, Ming; Shu, Jing (Frontiers in Endocrinology, 2023)
Primary ovarian insufficiency (POI) is among the foremost causes of women infertility due to premature partial or total loss of ovarian function. Resistant ovary syndrome (ROS) is a subtype of POI manifested as normal ovarian reserve but insensitive to gonadotropin stimulation. Inactivating variants of follicle-stimulating hormone receptor (FSHR), a class A G-protein coupled receptor, have been associated with POI and are inherited via an autosomal recessive pattern. In this study, we investigated the genetic causes of a primary infertility patient manifested as POI with ROS, and elucidated the structural and functional impact of variants of uncertain significance. Next-generation sequencing (NGS) combined with Sanger sequencing revealed novel compound heterozygous FSHR variants: c.1384G>C/p.Ala462Pro and c.1862C>T/p.Ala621Val, inherited from her father and mother, respectively. The two altered amino acid sequences, localized in the third and seventh transmembrane helix of FSHR, were predicted as deleterious by in silico prediction. In vitro experiments revealed that the p.Ala462Pro variant resulted in barely detectable levels of intracellular signaling both in cAMP-dependent CRE-reporter activity and ERK activation and displayed a severely reduced plasma membrane receptor expression. In contrast, the p.Ala621Val variant resulted in partial loss of receptor activation without disruption of cell surface expression. In conclusion, two unreported inactivating FSHR variants potentially responsible for POI with ROS were first identified. This study expands the current phenotypic and genotypic spectrum of POI.